P200 A qualitative european survey of patients perceptions of current management of idiopathic pulmonary fibrosis. (14th November 2013) - Russell, AM; Vancheri, C; Maronati, M; Giot, C
Abstract : Objectives: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, fibrotic lung associated with significant mortality. There has been a marked increased interest in IPF and new emerging therapies have been shown to improve either the survival or quality of life for some people with IPF. This study aimed to explore patient's perceptions of current therapy & management of IPF, specifically pirfenidone as the first approved treatment. Methods: Patients diagnosed with IPF according to current criteria and prescribed pirfenidone by one of 3 European specialist ILD centres were enrolled in a qualitative survey. One-to-one in-depth interviews were conducted between September and October 2012. Results: 45 Participants (71% male; mean age 68.5 years). Mean time from diagnosis to interview 3.5 years. Post diagnosis, 68% of patients felt their knowledge about IPF severity, treatments and prognosis increased markedly, predominantly through the use of the internet. 32% of patients relied exclusively on information gained from the consultation and demonstrated a lack of understanding of the disease and its process. For all patients the transition to oxygen therapy signalled a significant change impacting upon the view of their future. O2 therapy was associated with social exposure of disease, often with feelings of "shame" (35%). This impacted quality of life: "restricting activity"; "making simple tasks difficult….even talking" and was associated with impaired emotional well-being (Figure 1). There was an overwhelming lack of psychological support (79%) as patients struggled to comprehend the disease process. Patients spontaneously identified specific approaches that could improve their disease experience. Pirfenidone was well tolerated and offered hope to the majority of patients (83%). However 44% of patients reported anxieties re continuing access. Conclusions: Post diagnosis, many patients demonstrate resourcefulness in accessing information and have realistic expectations of how to improve care. There is a need to improve the information given in the consultation to improve subsequent understanding and to increase provision of psychological support particularly when prescribing O2 therapy. The availability of pirfenidone was perceived by patients to offer hope and reassurance. Strategies to reduce the delay in diagnosis and standardise access to information and therapies are needed.